Investigation of the Psychometric Characteristics of the Turkish Version of the Pediatric Nurse Parent Partnership Scale for Pediatric Nurses - Dilek Demir-Kösem; Çiğdem Müge Haylı; Şenay Demir; Neşe Ataman-Bor (Florence Nightingale Journal of Nursing)
AIM: The objective of this study was to adapt the pediatric nurse parent partnership scale into Turkish and assess its validity and reliability.